Human Resources Development at Tumela Mine - Mphahlele, Matuku (University of the Witwatersrand, Johannesburg, 2014)
In the context of the South African mining and mineral sector this study explores the human resource development measures to transform mentoring programmes at Tumela Mine. Despite the legislative stipulations that seek to promote equitable access to participation in the creation, development and sharing of the South African economy and natural resources through the establishment of a workplace environment conducive for learning to take place, little is known on how Tumela Mine implements mentoring programmes to foster effective human resource development. The study explored and analysed participants’ perceptions regarding the implementation of the Tumela Mine Mentoring Programme. The research was conducted through the use of a case study approach, and primary data was collected from respondents, and secondary data was gathered from relevant policies, minutes of meetings and company annual reports. The research questioned the successful aspects in the Human Resource Development unit, challenges and management’s responses to impediments to the implementation of mentoring programmes at Tumela Mine. The findings indicate that two key issues to improve implementation of mentoring programmes at the Tumela Mine are a transformational style of management and strategic repositioning of the mentoring programmes. The research argues that although company corporate strategic policy formulation and planning seek to promote equal participation of all employees in mentoring relationships, programme interventions at an operational level make it difficult to promote mentoring programmes. The key recommendation is that in order to implement effective mentoring programmes the company should review the corporate business strategy focused on strategic repositioning of mentoring programmes and inspire visionary leadership to implement a transformational style of management.
MM (P&DM) thesis
Keywords: Human resource development; Mines and mining; South African mining and mineral sector; Tumela Mine; Tumela Mine Mentoring Programme